Zinc Preconditioning Provides Cytoprotection following Iodinated Contrast Media Exposure in In Vitro Models. (17th February 2021) - Perera, Marlon; Ischia, Joseph; Bolton, Damien; Shulkes, Arthur; Baldwin, Graham S.; Patel, Oneel
Abstract : Introduction & Objectives . Contrast media (CM) causes renal injury through both direct cellular injury (cytotoxicity) and regional vascular changes (renal hypoxia) mediated by reactive oxygen species (ROS). Zinc may be able to provide protection against CM-induced cytotoxicity due to its indirect antioxidant properties and subsequent effect on ROS. We aimed to determine the protective role of zinc preconditioning against contrast-induced renal injury in vitro . Methods . Normal human proximal renal kidney cells (HK-2) were preconditioned with either increasing doses of ZnCl2 or control. Following this preconditioning, cells were exposed to increasing concentrations of Iohexol 300 mg I2 /ml for four hours. Key outcome measures included cell survival (MTT colorimetric assay) and ROS generation (H2 DCFDA fluorescence assay). Results . Contrast media induced a dose-dependent reduction in survival of HK-2 cells. Compared to control, contrast media at 150, 225, and 300 mg I2 /ml resulted in 69.5% (SD 8.8%), 37.3% (SD 4.8%), and 4.8% (SD 6.6%) cell survival, respectively (p < 0.001 ). Preconditioning with 37.5  μ M and 50  μ M ZnCl2 increased cell survival by 173% (SD 27.8%) (p < 0.001 ) and 219% (SD 32.2%) (p < 0.001 ), respectively, compared to control preconditioning. Zinc preconditioning resulted in a reduction of ROS generation. Zinc pre-conditioning with 37.5  μ M  μ M ZnCl2 reduced ROS generation by 46% (p < 0.001 ) compared to control pre-conditioning. Conclusions . Zinc preconditioning reduces oxidative stress following exposure to radiographic contrast media which in turn results in increased survival of renal cells. Translation of this in vitro finding in animal models will lay the foundation for future use of zinc preconditioning against contrast induced nephropathy.